Inter-subject correlation of brain hemodynamic responses during watching a movie: localization in space and frequency - Kauppi, Jukka-Pekka; Jääskeläinen, Iiro P.; Sams, Mikko; Tohka, Jussi (Frontiers in Neuroinformatics, 2010)
Cinema is a promising naturalistic stimulus that enables, for instance, elicitation of robust emotions during functional magnetic resonance imaging (fMRI). Inter-subject correlation (ISC) has been used as a model-free analysis method to map the highly complex hemodynamic responses that are evoked during watching a movie. Here, we extended the ISC analysis to frequency domain using wavelet analysis combined with non-parametric permutation methods for making voxel-wise statistical inferences about frequency-band specific ISC. We applied these novel analysis methods to a dataset collected in our previous study where 12 subjects watched an emotionally engaging movie “Crash” during fMRI scanning. Our results suggest that several regions within the frontal and temporal lobes show ISC predominantly at low frequency bands, whereas visual cortical areas exhibit ISC also at higher frequencies. It is possible that these findings relate to recent observations of a cortical hierarchy of temporal receptive windows, or that the types of events processed in temporal and prefrontal cortical areas (e.g., social interactions) occur over longer time periods than the stimulus features processed in the visual areas. Software tools to perform frequency-specific ISC analysis, together with a visualization application, are available as open source Matlab code.